Developing Writing Materials Based on Eclectic Approach for Indonesian EFL Learners - Kurniasih Kurniasih; Henny Rahmawati (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
This study aims at developing writing materials based on Eclectic Approach for Indonesian EFL learners. The material is mainly developed and used for teaching essay writing for the third-semester students in the English Department, University of Islam Malang. It is also expected that the materials lower their anxiety as the findings of the preliminary study. This R and D research adapted development model proposed by Borg and Gall with the following procedures: need analysis, developing writing materials, expert validation, revision I, try out, revision II, and final product.  The final product of this research is an instructional material for Writing III course which was developed by considering students' needs, levels, suggestions, and feedback from experts. It also made used of the principles of Eclectic approach to lower their anxiety in writing essay, such as providing much exposure toward the target language with less pressure, integrating the good sides of various teaching techniques, using real-life situation to make learning more comprehensible, considering the students' needs, teaching and introducing contextual grammar and vocabulary, and integrating all language skills.